Itinerary of a pioneer - United Nations Educational, Scientific; Cultural Organization; Soledad Vallejos (The UNESCO Courier, 2023)
Free, engaged, stubborn, Victoria Ocampo was part of a gender perspective before the term even existed. By investing in the cultural milieu, she carved a new path and remains a reference point for the feminist movement.